Re-excision Rates and Local Recurrence in Breast Cancer Patients Undergoing Breast Conserving Therapy - Dieterich, M.; Dieterich, H.; Moch, H.; Rosso, C. (Geburtshilfe und Frauenheilkunde, 2012)
Background: Controversy continues over the impact of re-excision (RE) on local recurrence (LR) in patients with invasive breast cancer. Patients and Methods: We investigated factors which could effect RE rates in patients undergoing breast-conserving or oncoplastic surgery. Between 2000 and 2003, 489 patients with stage pT1-pT2 or pN0/1 tumors were evaluated. 74 patients fulfilled the inclusion criteria. Patients were categorized into 3 groups: no RE (n = 25), RE during primary surgery (n = 28), and RE performed during secondary or even tertiary procedure (n = 21). All tumor slides were re-evaluated by a pathologist specializing in breast cancer. Results: Mean follow-up was 70 months with an overall LR rate of 4.1 %. Binary logistic regression revealed no tumor-specific risk factors for RE. There was no LR in the group of patients who did not have RE. There was one case of LR in the group of patients who had RE during primary surgery. Two cases of LR were observed in the group of patients who had two or more surgical procedures. Conclusion: New risk factors for increased RE rates were not observed, reflecting the inconsistent data on risk factors for RE. However, breast cancers should be excised in a single procedure and oncoplastic procedures should be considered.
Keywords: oncoplastic surgery; local recurrence; breast-conserving therapy; margin status; re-excision; breast cancer